2007
DOI: 10.1098/rsbl.2007.0334
|View full text |Cite
|
Sign up to set email alerts
|

Larval rearing environment affects several post-copulatory traits in Drosophila melanogaster

Abstract: In Drosophila melanogaster, accessory gland proteins (Acps) that a male transfers during mating affect his reproductive success by altering the female's behaviour and physiology. To test the role of male condition in the expression of Acps, we manipulated the pre-adult environment and examined adult males for relative transcript abundance of nine Acps, and for post-copulatory traits that Acps influence. Larval culture density had no effect on any measured trait. Larval nutrient availability impacted the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
120
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 13 publications
12
120
4
Order By: Relevance
“…There are many possible explanations for the difference in findings across studies. First, environmental conditions can have a very large effect on egg laying rates (McGraw et al 2007;Fricke et al 2010), and it is almost certain the conditions of our study differed from those of the earlier study. Second, the experimental design we employed involved egg counts only on the first 2 days after the first mating, whereas the study reported egg counts over a longer period.…”
Section: Discussioncontrasting
confidence: 54%
“…There are many possible explanations for the difference in findings across studies. First, environmental conditions can have a very large effect on egg laying rates (McGraw et al 2007;Fricke et al 2010), and it is almost certain the conditions of our study differed from those of the earlier study. Second, the experimental design we employed involved egg counts only on the first 2 days after the first mating, whereas the study reported egg counts over a longer period.…”
Section: Discussioncontrasting
confidence: 54%
“…Although it seems unlikely that subtle food batch differences or even relatively large variation in larval density are the cause (McGraw et al 2007), these results do point to both a strong genetic and environmental component to sperm competitive ability and highlight the complex nature of these phenotypes.…”
Section: Discussionmentioning
confidence: 77%
“…Empirical studies involving experimental manipulations of condition generally support this prediction, reporting that highcondition males produce larger ejaculates (Gwynne 1990;Delisle & Bouchard 1995;Watanabe & Hirota 1999;Jia et al 2000;Ferkau & Fisher 2006;Lewis & Wedell 2007;Blanco et al 2009; but see Wedell 1993), transfer more sperm (Fedina & Lewis 2006;McGraw et al 2007;Perez-Staples et al 2008), and produce more ejaculate-derived nuptial gifts (Jia et al 2000; but see Wedell 1993).…”
Section: Introductionmentioning
confidence: 72%